2011
DOI: 10.1007/s13361-010-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on the Frontier of Photodissociation

Abstract: The development of new ion activation/dissociation methods is motivated by the need for more versatile ways to characterize structures of ions, especially in the growing arena of biological mass spectrometry in which better tools for determining sequences, modifications, interactions, and conformations of biopolymers are essential. Although most agree that collision-induced dissociation (CID) remains the gold standard for ion activation/dissociation, recent inroads in electron-and photon-based activation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 73 publications
0
44
0
2
Order By: Relevance
“…In fact, both UVPD and to an even greater extent UVPD/HCD generated a number of fragment ions that exhibited hydrogen migration suggesting that they were generated via a radical mechanism, which has been reported in other UVPD studies of other biopolymers. 41,4366 Although UVPD/HCD did not provide any new structural information over UPVD, the dissociation efficiency of UVPD/HCD was greater than UVPD alone and the array of observed fragment ions exceeded that of HCD alone, thus providing information about both the lipid A and inner core regions of Kdo 2 -Lipid A. One notable difference between CID, HCD, UVPD and UVPD/HCD is the variation in the relative abundances of doubly charged fragment ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, both UVPD and to an even greater extent UVPD/HCD generated a number of fragment ions that exhibited hydrogen migration suggesting that they were generated via a radical mechanism, which has been reported in other UVPD studies of other biopolymers. 41,4366 Although UVPD/HCD did not provide any new structural information over UPVD, the dissociation efficiency of UVPD/HCD was greater than UVPD alone and the array of observed fragment ions exceeded that of HCD alone, thus providing information about both the lipid A and inner core regions of Kdo 2 -Lipid A. One notable difference between CID, HCD, UVPD and UVPD/HCD is the variation in the relative abundances of doubly charged fragment ions.…”
Section: Resultsmentioning
confidence: 99%
“…As a promising alternative, UVPD is a higher energy activation method that has demonstrated advantages over CID for characterization of a wide range of biopolymers (including lipids, proteins, peptides, nucleic acids, and glycans). 41,4366 Hybrid activation methods consisting of UVPD in conjunction with CID or electron transfer dissociation (ETD) have also been developed as a means to yield even richer fragmentation patterns. 44,46 We have explored UVPD at 193 nm for characterization of glycolipids, including lipid A, and found that UV photoexcitation promotes extensive C-C, C-N, C-O, glycosidic and cross-ring cleavages which contribute to the highly informative fragmentation patterns observed upon UVPD.…”
Section: Introductionmentioning
confidence: 99%
“…Many mass spectrometry-based experiments, not just ion traps, have since exploited the use of coherent laser light sources for photodissociation spectroscopy -both UV and IR -as well as for photodissocation of molecules for structural characterization. [23][24][25][26][27] UV-vis PD action spectroscopy of ions is becoming increasingly prevalent due to advances and commercial availability of both ion trapping technologies and tunable laser sources. The linear quadrupole ion trap [28,29] is particularly well suited to PD experiments [30] as it provides a trapped ion ensemble with large number densities, located in a tight cylindrical ion packet confined around the ion-trap principal axis (z-axis), [31] other well-suited configurations include multipole traps [32,33] and storage rings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, photodissociation methods for MS/MS have achieved some success in this regard [116,117]. Irradiation of trapped ions with infrared photons to bring about IRMPD is one such method [118].…”
Section: Use Of a Single Ms/ms Methodsmentioning
confidence: 99%